Investigation of quality of data input in life cycle cost analysis of rigid pavement type - Ahmad Jasmi, Siti Zulaiha; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2015)
Roads in Malaysia are divided into two main categories, which are flexible and rigid pavements. The cost for constructing and maintaining the roads and highways is very high. Due to the limitation of budget, the life cycle cost (LCC) analysis for cost estimation of rigid pavement is important. However, one of the major obstacles of implementing LCC analysis in the rigid pavement is lack of current and reliable data inputs. Most of the scholars and estimators focused on the LCC conversion but very little emphasis is given on the availability, accessibility, currency and reliability of data inputs in producing reliable LCC outputs. The objective if this paper is to present the proposal of research to investigate the quality of cost data input for LCC analysis of rigid pavement type in Klang Valley, Malaysia. The Federal Roads in Klang Valley are chosen as the subject matter of the study. The methodology chosen for the study will be the qualitative research strategy that includes two approaches, i.e. secondary data collection (literature review) and primary data collection (Focus Group Discussion). The expected outcome of this study will be a developed step-bystep methodology that will be proposed to improve the quality of data inputs in LCC analysis of rigid pavement type.